Electrochemical behaviour of CuxMo6S8 thin films synthesized by CSD. (10th December 2017) - Boursicot, Stéphanie; Bouquet, Valérie; Bombard, Aude; Langer, Michaela; Boulanger, Clotilde; Guilloux-Viry, Maryline
Highlights: Cu2 Mo6 S8 thin films are achieved by CSD on conducting and insulating substrates The Cu2 Mo6 S8 films are suitable for electrochemical reversible insertion of Cd 2+ A detection of Cd 2+ with a sensitivity of at least 10 −6 M/L was observed The electrochemical insertion cyclability is higher than 100 cycles Potentiality of the films for a portable electrochemical sensor for heavy metal ions Abstract: Cu2 Mo6 S8 thin films were synthesized on various substrates (R-sapphire, Mo, TiN/Si, Ti/Si and vitreous carbon) using chemical solution deposition from intermediate oxides obtained by the polymeric precursor method. The structural and microstructural characteristics of the films were studied by X-ray diffraction and field emission scanning electron microscopy. The electrochemical intercalation/de-intercalation was evaluated on these films by cyclic voltammetry and differential pulse voltammetry in aqueous CdSO4 10 −1, 10 −5 and 10 −6 M solutions. This work demonstrated the intercalation capacity of the Cu2 Mo6 S8 films and the best results were obtained on TiN/Si: fast and reversible intercalation process, with cyclability higher than 100 cycles for an aqueous CdSO4 10 −1 M solution which demonstrates the possibility to re-use the Cu2 Mo6 S8 electrode. At lower concentration, differential pulse voltammetry method allowed to detect Cd 2+ with a minimal sensitivity of the order of 10 −6 M. These results offer promising perspectives for intercalation/de-intercalation of other heavy metal ions at low concentrations in Cu2 Mo6 S8 films on TiN/Si and thus for future applications such as miniaturized electrochemical sensors.